Son of a witch : vol. 2 ; novel - Maguire, Gregory (New York : HARPER, an Imprint of Harper CollinsPublisher, 2008)
Years after the death of Elphaba, the Wicked Witch of the West, a young man named Liir, rumored to be Elphaba's son, is discovered by the nuns of Saint Gilda and revived by the mysterious foundling Candle
Originally published: New York : ReganBooks, c2005
Sequel to: Wicked
Keywords: Fantasy fiction; Fantasy fiction